Social isolation stress and chronic glutathione deficiency have a common effect on the glutamine‐to‐glutamate ratio and myo‐inositol concentration in the mouse frontal cortex. Issue 5 (28th July 2017) - Corcoba, Alberto; Gruetter, Rolf; Do, Kim Q.; Duarte, João M.N.
Abstract : A mouse model with chronic glutathione deficit induced by knockout (−/−) of the glutamate‐cysteine ligase modulatory subunit ( Gclm ) was exposed to social isolation stress from weaning to post‐natal day 65. Using magnetic resonance spectroscopy at high‐field (14.1 T), we analysed the neurochemical profile in the frontal cortex. Our results indicate that both impaired glutathione synthesis and social isolation stress, which are risk factors for neuropsychiatric disorders, contribute to alterations of myo ‐inositol concentration and the ratio of glutamine‐to‐glutamate in the mouse frontal cortex. Abstract: Environmental stress can interact with genetic predisposition to increase the risk of developing psychopathology. In this work, we tested the hypothesis that social isolation stress interacts with impaired glutathione synthesis and have cumulative effects on the neurochemical profile of the frontal cortex. A mouse model with chronic glutathione deficit induced by knockout (−/−) of the glutamate‐cysteine ligase modulatory subunit ( Gclm ) was exposed to social isolation stress from weaning to post‐natal day 65. Using magnetic resonance methods at high‐field (14.1 T), we analysed the neurochemical profile in the frontal cortex, brain size and ventricular volume of adult animals. Glutathione deficit was accompanied by elevated concentrations of N ‐acetylaspartate, alanine, and glutamine, as well as the ratio of glutamine‐to‐glutamate (Gln/Glu), and by a reduction in levels of myo‐ inositol and choline‐containing compounds in the frontal cortex of −/− animals with respect to wild‐type littermates. Although there was no significant interaction between social isolation stress and glutathione deficiency, mice reared in isolation displayed lower myo‐ inositol concentration (−8.4%, p < 0.05) and larger Gln/Glu (+7.6%, p < 0.05), relative to those in group housing. Furthermore, glutathione deficiency caused a reduction in whole brain volume and enlargement of ventricles, but social isolation had no effect on these parameters. We conclude that social isolation caused neurochemical alterations that may add to those associated to impaired glutathione synthesis.